Parallel single-cell analysis of active caspase-3/7 in apoptotic and non-apoptotic cells - Ledvina, Vojtěch; Janečková, Eva; Matalová, Eva; Klepárník, Karel (Analytical and bioanalytical chemistry, 2017)
Analysing the chemical content of individual cells has already been proven to reveal unique information on various biological processes. Single-cell analysis provides more accurate and reliable results for biology and medicine than analyses of extracts from cell populations, where a natural heterogeneity is averaged. To meet the requirements in the research of important biologically active molecules, such as caspases, we have developed a miniaturized device for simultaneous analyses of individual cells. A stainless steel body with a carousel holder enables high-sensitivity parallel detections in eight microvials. The holder is mounted in front of a photomultiplier tube with cooled photocathode working in photon counting mode. The detection of active caspase-3/7, central effector caspases in apoptosis, in single cells is based on the bioluminescence chemistry commercially available as Caspase-Glo® 3/7 reagent developed by Promega. Individual cells were captured from a culture medium under microscope and transferred by micromanipulator into detection microvial filled with the reagent. As a result of testing, the limits of detection and quantification were determined to be 0.27/0.86 of active caspase-3/7 content in an average apoptotic cell and 0.46/2.92 for non-apoptotic cells. Application potential of this technology in laboratory diagnostics and related medical research is discussed. Graphical abstract Miniaturized device for simultaneous analyses of individual cells.
Keywords: luminiscenční měření; Enzyme Assays; Luminescent Measurements; Bioluminescence; Equipment Design; analýza jednotlivých buněk; Caspase 7; enzymatické testy; Single-Cell Analysis; zvířata; Cells, Cultured; myši; Caspase-3/7; kaspasa 3; Mice; apoptóza; Caspase 3; kaspasa 7; kultivované buňky; design vybavení; Animals; Single-cell analysis; Apoptosis